2019
DOI: 10.1016/j.dcn.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Hand or spoon? Exploring the neural basis of affective touch in 5-month-old infants

Abstract: In adults, affective touch leads to widespread activation of cortical areas including posterior Superior Temporal Sulcus (pSTS) and Inferior Frontal Gyrus (IFG). Using functional Near Infrared Spectroscopy (fNIRS), we asked whether similar areas are activated in 5-month-old infants, by comparing affective to non-affective touch. We contrasted a human touch stroke to strokes performed with a cold metallic spoon. The hypothesis that adult-like activation of cortical areas would be seen only in response to the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The fundamental shift from spontaneous to evoked somatosensory activity occurs in the third trimester (Fabrizi et al, 2011), and after birth, the intensity and valence of touch experiences continue to shape somatosensory development (Maitre et al, 2017). In infants, gentle stroking preferentially activates both S1 and the posterior insular cortex; these regions are slightly different from those activated in adults, which may reflect an experience-dependent shift in the localization of affectionate touch processing (Jönsson et al, 2018;Pirazzoli et al, 2019;Tuulari et al, 2019). Lower-level processes of sensation and perception lay the foundation for development of higher-level cognitive functions, therefore early experiences of touch also contribute toward the maturation of neural circuitry for complex cognitive and social function.…”
Section: A Somatosensory Tuningmentioning
confidence: 99%
“…The fundamental shift from spontaneous to evoked somatosensory activity occurs in the third trimester (Fabrizi et al, 2011), and after birth, the intensity and valence of touch experiences continue to shape somatosensory development (Maitre et al, 2017). In infants, gentle stroking preferentially activates both S1 and the posterior insular cortex; these regions are slightly different from those activated in adults, which may reflect an experience-dependent shift in the localization of affectionate touch processing (Jönsson et al, 2018;Pirazzoli et al, 2019;Tuulari et al, 2019). Lower-level processes of sensation and perception lay the foundation for development of higher-level cognitive functions, therefore early experiences of touch also contribute toward the maturation of neural circuitry for complex cognitive and social function.…”
Section: A Somatosensory Tuningmentioning
confidence: 99%
“…Moreover, a recent study reported activation of insular cortex in response to affective touch from 2 months of life (Jönsson et al, 2018) suggesting that infants are sensitive to interoceptive properties of affective touch from the earlies stages of life. However, other evidence suggest that the specialization of cortical processing of affective touch might still be ongoing during early infancy (Kida and Shinohara, 2013;Miguel et al, 2017;Pirazzoli et al, 2019). Thus, it is possible that while cortical responses to touch velocity, which selectively activate the C-tactile system, are already evident soon after birth (Jönsson et al, 2018), sensitivity to other perceptual properties that convey specific information about human contact, such as texture, body, and temperature, require more time to develop (Pirazzoli et al, 2019).…”
Section: Groupmentioning
confidence: 99%
“…However, other evidence suggest that the specialization of cortical processing of affective touch might still be ongoing during early infancy (Kida and Shinohara, 2013;Miguel et al, 2017;Pirazzoli et al, 2019). Thus, it is possible that while cortical responses to touch velocity, which selectively activate the C-tactile system, are already evident soon after birth (Jönsson et al, 2018), sensitivity to other perceptual properties that convey specific information about human contact, such as texture, body, and temperature, require more time to develop (Pirazzoli et al, 2019). According to a neurocostructivism perspective, early interoceptive sensitivity to affective touch may undergo a gradual process of functional specialization and cortical localization that provide the neurophysiological foundation for the emergence of socio-affective meaning of interpersonal contact (Johnson, 2001(Johnson, , 2011.…”
Section: Groupmentioning
confidence: 99%
“…This link is partially explained by sensitive and responsive parenting behaviours, as mothers tend to use different types of touch as a function of the type of cue communicated by the infant and as a result of the infant's temperament or disposition (Ferber et al, ). As argued, the study of emotional and motivational aspects of touch, which has been referred to as affective touch (see McGlone et al, ), has been emphasized in recent years (see Cascio et al, for a review) as well as the neurophysiological underpinnings of affective touch in early experience in humans (see for example Jönsson et al, ; Pirazzoli, Lloyd Fox, Braukmann, Johnson, & Gliga, ; Tuulari et al, ). However, despite this recent work, as stated, there is an overall failure of the attachment and maternal sensitivity literature to include the type of precise definition of touch present in other disciplines of science.…”
Section: Touch In Human Primatesmentioning
confidence: 99%